2022
DOI: 10.1186/s12951-021-01207-6
|View full text |Cite|
|
Sign up to set email alerts
|

Atom-precise fluorescent copper cluster for tumor microenvironment targeting and transient chemodynamic cancer therapy

Abstract: Background Reactive oxygen species (ROS) have been widely studied for cancer therapy. Nevertheless, instability and aspecific damages to cellular biomolecules limit the application effect. Recently, significant research efforts have been witnessed in the flourishing area of metal nanoclusters (NCs) with atomically precise structures for targeted release of ROS but few achieved success towards targeting tumor microenvironment. Results In this work, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Illustrated lattice fringes (Figure f) and IFFT (Figure g,h) results reveal a lattice spacing of 0.208 nm, corresponding to the (111) planes of copper. And combining with the previous XRD data, it can be obtained that Cu is present in the carbon framework in the form of Cu clusters. , HADDF-EDS elemental mapping analysis (Figure i) strengthens the case for a uniform distribution of C, N, Co, and Cu on the carbon matrix. Integrating these findings with XRD spectra unambiguously confirms the chemical bonding of Co with the substrate.…”
Section: Resultssupporting
confidence: 66%
“…Illustrated lattice fringes (Figure f) and IFFT (Figure g,h) results reveal a lattice spacing of 0.208 nm, corresponding to the (111) planes of copper. And combining with the previous XRD data, it can be obtained that Cu is present in the carbon framework in the form of Cu clusters. , HADDF-EDS elemental mapping analysis (Figure i) strengthens the case for a uniform distribution of C, N, Co, and Cu on the carbon matrix. Integrating these findings with XRD spectra unambiguously confirms the chemical bonding of Co with the substrate.…”
Section: Resultssupporting
confidence: 66%
“…Therefore, to develop a treatment through ferroptosis in cancer nanomedicine, research on the possibility and performance of anticancer treatment using nanoparticles, as well as research on the mechanism of ferroptosis are continuously and actively being reported. [18][19][20][21][22][23] In clinical cancer treatment, X-rays are a commonly and widely used radiation therapy and have remained one of the standard cancer treatments for decades because of their good effectiveness. In fact, 50% of cancer patients receive radiation therapy, and even though it is the cornerstone of cancer treatment, complete response to cancer treatment is still challenging due to radiation resistance, remarking the necessity for radiosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to develop a treatment through ferroptosis in cancer nanomedicine, research on the possibility and performance of anticancer treatment using nanoparticles, as well as research on the mechanism of ferroptosis are continuously and actively being reported. [ 18–23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] However, the high reactivity of surface atoms in most nanoclusters may result in autonomous aggregation in physiological environments, potentially reducing their overall catalytic activity. [21][22][23][24][25] Therefore, it remains an urgent challenge to design nanocatalysts that can realize effective CDT in complex physiological environments.…”
Section: Introductionmentioning
confidence: 99%